2013
DOI: 10.1371/journal.pone.0070567
|View full text |Cite
|
Sign up to set email alerts
|

Direct Diabetes-Related Costs in Young Patients with Early-Onset, Long-Lasting Type 1 Diabetes

Abstract: ObjectiveTo estimate diabetes-related direct health care costs in pediatric patients with early-onset type 1 diabetes of long duration in Germany.Research Design and MethodsData of a population-based cohort of 1,473 subjects with type 1 diabetes onset at 0–4 years of age within the years 1993–1999 were included (mean age 13.9 (SD 2.2) years, mean diabetes duration 10.9 (SD 1.9) years, as of 31.12.2007). Diabetes-related health care services utilized in 2007 were derived from a nationwide prospective documentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…Our results, however, show that there was a close association between the diabetes‐specific impact score and the glycemic control of patients with high‐risk HbA1c. This finding has the important clinical implication that QoL screening and intervention should preferentially be targeted to patients in poor glycemic control, in particular against the background that these patients have the greatest morbidity, risk of diabetic complications, and per capita costs . Further, it may be assumed that the future glycemic control will be decisively influenced by current HbA1c and the close relationship between HbA1c and QoL, and it appears all the more important to optimize HbA1c and QoL synchronously in childhood and later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Our results, however, show that there was a close association between the diabetes‐specific impact score and the glycemic control of patients with high‐risk HbA1c. This finding has the important clinical implication that QoL screening and intervention should preferentially be targeted to patients in poor glycemic control, in particular against the background that these patients have the greatest morbidity, risk of diabetic complications, and per capita costs . Further, it may be assumed that the future glycemic control will be decisively influenced by current HbA1c and the close relationship between HbA1c and QoL, and it appears all the more important to optimize HbA1c and QoL synchronously in childhood and later in life.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that in adults, diabetes imposes a large economic burden; however, there is very little information on the cost of diabetes in children and adolescents, especially for those with type 2 diabetes (see ISPAD Clinical Practice Consensus Guidelines 2018: Type 2 diabetes mellitus in youth DOI: 10.1111/pedi.12719). Yet such information is critical when assessing the economic burden of disease and evaluating the economic efficiency of diabetes prevention and control programs in this population.…”
Section: Overall Analysis Of Diabetes Health Care Costs and Utilizationmentioning
confidence: 99%
“…However, there is plenty of evidence on this issue in the international literature [50]. For example, evidence has shown that compared with NPH, insulin analogues decreases the risk of severe hypoglycemia episodes by 38% (OR 0.62, 95% CI 0.42–0.91) [4], the risk of nocturnal hypoglycemia episodes by 46% (p = 0.04) [51], the risk of hospitalization due to the first severe hypoglycemic event by 21.7% (95% CI 9.6–32.1%,p<0.001) [52], the risk of hypoglycemic coma recurrence by 36.3% (95% CI 8.9–55.5%, p = 0.014) [52], hospitalizations by 49% [53], the incidence of macrovascular complications by 48% [54], and annual costs [55].…”
Section: Discussionmentioning
confidence: 99%